Pengaruh Pembangunan Jembatan Tunggul Mas Terhadap Kinerja Ruas Jalan Tlogomas Kota Malang - Da Silva , Jenia Hoar Pinto; Primasworo, Rifky Aldila; Sa'dillah , M. (Prosiding SENTIKUIN (Seminar Nasional Teknologi Industri, Lingkungan dan Infrastruktur), 2023)
Transportation is an important part of human life. Transportation is closely linked to all human activities, including the acquisition of products and services for many reasons. The purpose of this study is to assess the performance of the road, assess the impact of bridge construction, and find a feasible alternative solution. This research belongs to the field of quantitative descriptive research. It uses a hypothesis verification method, beginning with deductive reasoning to formulate hypotheses and then conducting field tests. The Tlogomas Road section of Malang City is observed to be busy on Tuesdays at 06.00 to 07.00. So far we have been able to achieve a capacity value (C) of 2,775 skr/h and a degree of saturation (DJ) value of 0.93, higher than the DJ value set in PKJI 2014 (DJ > 0.85). Therefore, the level of service is categorized as E, indicating inconsistent flow with periodic decreases in speed and demand approaching its maximum capacity. Based on the study results obtained through the use of SPSS, it can be concluded that the construction of the Tunggul Mas bridge has a significant influence on the performance of the Tlogomas road section. In section 2, it seems that the eastern region, X1 (motorcycles), is the most affected. The estimated t table value of 2.650 is much greater than the t table value of 0.005. Alternative solutions used include the installation of warning signs prohibiting parking on the roadside, as well as the application of yellow box intersection markings at the Tlogomas intersection in Malang City.